The Current State of Formation of Digital Competence of Bachelors in Management by Means of Information Technologies - Dehtiarov, Volodymyr (Educological discourse, 2025)
Digital competence is one of the key factors of a manager's professional success in the conditions of modern digital transformation. It provides the ability to adapt to new challenges, quickly make informed decisions, use modern information and communication technologies (ICT) to optimize management processes and create additional value for the organization. It has been determined that the digital competence of future managers covers several key aspects. First, it is information literacy, which involves the ability to work with information from various sources, using analytical tools such as BI systems or CRM systems. The second is digital communication and collaboration, which includes the use of video conferencing platforms (Microsoft Teams, Zoom), team management tools (Slack), and social media to interact and build connections. Thirdly, an important component is technological awareness, which covers the use of office software, cloud services and specialized platforms for project management (Trello, Asana). In addition, digital competence covers analytical thinking, working with big data (Big Data) and visualizing information using programs (Tableau, Power BI). Equally important aspects are critical thinking and the safe use of digital technologies in compliance with the principles of cyber security. Innovation and flexibility are the basis for adapting to new digital trends and integrating innovation into business practices. Digital leadership, in turn, is aimed at forming a digital culture in the organization and motivating employees to use digital technologies to achieve strategic goals. The current state of Bachelors’ training in management in Ukraine indicates significant achievements and also highlights a number of challenges. According to research, most students have basic digital skills, but in-depth knowledge in the field of digital management, such as working with CRM systems, analytical platforms and cyber security technologies, needs further improvement. International studies confirm the importance of integrating digital disciplines into educational programs and focusing on modern standards of digital literacy. To improve the training of Bachelors in management, it is proposed to develop integrated educational programs on digital business transformation, conduct practical classes using modern software products, introduce internships in companies that actively use digital technologies, and create digital laboratories for students.